Analisis Pengetahuan Mahasiswa Akuntansi dan Manajemen Mengenai Perkembangan Penganggaran dan Pembiayaan Pemerintah Daerah - Kamela, Hurian; Alam, Ryan Saputra; Pujia, Dede Puspa; Susilowati, Susilowati; Yahya, Adibah (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
The purpose of this study is to initiate the relationship between the development of local government budgeting and the level of knowledge of students in the Accounting and Management study program. The study focuses on public budgets, changes in laws, performance-based budgeting, and the application of information technology in the budget process. This study employed a quantitative, descriptive-comparative approach. Data were collected through questionnaires distributed to final-year students who had taken courses related to the public sector. In general, the study's results indicate that students possess sufficient knowledge. However, there is a significant difference between accounting and management students: accounting students tend to have a better understanding of concepts and strategies. In comparison, management students tend to have a better understanding of accounting techniques and procedures. Additionally, components of the academic experience and sources of information influence the level of knowledge among respondents. To better prepare students to face challenges in the field of local public finance, this study recommends adopting a practice-based curriculum and incorporating real-world problems into the learning process.